TIGIT: A promising target to overcome the barrier of immunotherapy in hematological malignancies - Jin, Shenhe; Zhang, Ye; Zhou, Fengping; Chen, Xiaochang; Sheng, Jianpeng; Zhang, Jin (Frontiers in Oncology, 2022)
Immune evasion through up-regulating checkpoint inhibitory receptors on T cells plays an essential role in tumor initiation and progression. Therefore, immunotherapy, including immune checkpoint inhibitor targeting programmed cell death protein 1 (PD-1) and chimeric antigen receptor T cell (CAR-T) therapy, has become a promising strategy for hematological malignancies. T cell immunoreceptor with immunoglobulin and ITIM domain (TIGIT) is a novel checkpoint inhibitory receptor expressed on immune cells, including cytotoxic T cells, regulatory T cells, and NK cells. TIGIT participates in immune regulation via binding to its ligand CD155. Blockage of TIGIT has provided evidence of considerable efficacy in solid tumors in preclinical research and clinical trials, especially when combined with PD-1 inhibition. However, the mechanism and function of TIGIT in hematological malignancies have not been comprehensively studied. In this review, we focus on the role of TIGIT in hematological malignancies and discuss therapeutic strategies targeting TIGIT, which may provide a promising immunotherapy target for hematological malignancies.